Impact of metabolic risk factors on colorectal cancer burden in China: a comprehensive analysis of trends from 1990 to 2021 - Zhan, Zhouwei; Zheng, Hanchen; Chen, Chuying; Yu, Jiami; Zheng, Lina; Yang, Chunkang; Guo, Zengqing; Chen, Bijuan (Frontiers in Nutrition, 2026)
BackgroundColorectal cancer (CRC) represents a significant public health challenge in China. With the rising prevalence of metabolic disorders such as obesity and diabetes, it is essential to understand the long-term burden of CRC attributable to metabolic risks.MethodsThis study utilized data from the Global Burden of Disease (GBD) 2021 to estimate the burden of CRC attributable to metabolic risks in China from 1990 to 2021. Metrics analyzed included deaths, disability-adjusted life years (DALYs), years of life lost (YLLs), and years lived with disability (YLDs), stratified by age, sex, and year. Joinpoint regression, age-period-cohort analysis, and decomposition methods were employed to explore temporal trends and underlying drivers.ResultsIn 2021, CRC attributable to metabolic risks caused 36,462 deaths and 902,557 DALYs in China, with significantly higher burdens among men. The age-standardized death and DALY rates were 2.36 and 56.09 per 100,000 in men, respectively, nearly double those in women. Between 1990 and 2021, age-standardized rates of mortality, DALYs, YLDs, and YLLs increased significantly (AAPC > 0; p < 0.05), especially in males and older adults. High body mass index (BMI) showed a significantly steeper rise in ASRs than high fasting plasma glucose (HFPG) (p < 0.05), although HFPG exhibited smaller—and in some strata non-significant—changes (p ≥ 0.05). Compared to global trends, China experienced a sharper rise in CRC burden, particularly in YLDs. Joinpoint regression identified significant increases in mortality and DALYs (p < 0.05), with an acceleration after ~2007, while age-period-cohort analysis showed a pronounced increase in mortality and DALY rates among older age groups and more recent birth cohorts. Decomposition analysis indicated that in men, epidemiological changes primarily drove the increased burden, while in women, population aging and growth were dominant contributors.ConclusionThe burden of CRC attributable to metabolic risks has grown substantially in China, especially among men and older adults, with high BMI as the primary contributor. These findings highlight the urgent need for targeted prevention strategies addressing metabolic risk factors and sex-specific health interventions.